Sharpening Hölder's inequality - Hedenmalm, H.; Stolyarov, D.M.; Vasyunin, V.I.; Zatitskiy, P.B. (Journal of functional analysis, 2018)
We strengthen Hölder's inequality. The new family of sharp inequalities we obtain might be thought of as an analog of the Pythagorean theorem for the Lp-spaces. Our treatment of the subject matter is based on Bellman functions of four variables.